KARAKTERISTIK PENGAYAK GETAR DENGAN SUMBER EKSITASI POROS EKSENTRIK - Bur, M; Nazaruddin, Nazaruddin; Mahyuddin, A. I; Samudra, J (Mesin, 2000)
Vibrating screen is an equipment used to seperate material according to its particle size. It is usually operated in combination with a crusher. A vibrating screen prototype has been developed. This prototype, called as âPengayak Getar Semen Padang Prototipeâ0l" (PGSP PRO-01), employs an eccentric shaï¬â to excite the screen. The prototipe was designed to obtain several experimental parameters such as deck elevation, eccentric shaft rotational speed, screen capacity,types of material and screen mesh, gradation of material and spring stiffness. The characteristics of vibrating screen and material sieved may be determined experimentally. In this study, the performance of PGSP PRO-01 is examined by using silica sand, with a bulk density (Ï) of 1.54ton/m3, and material gradation of 50% of the grains larger than 5 mm, 35 % between 2.5 - 5 mm and 15% are less than 2.5 mm in size. Assuming a 92% screen eï¬iciency and a 0.32 m2 screening area, theoretical screen capacity of 7.5 ton-per-hour (tph) is obtained. Experimentally, optimum screening parameters obtained are 7.2tph capacity at 91.7% eï¬iciency resulting from a 900 rpm speed of eccentric shaï¬ and a 10Â° deck elevation.